Tanggung Jawab Pemerintah Terhadap Penanggulangan Covid-19 dalam Rangka Pelayanan Medis di Rumah Sakit - Ni Komang Rosi Triana Ayu Nuratih; I Ketut Kasta Arya Wijaya; Ida Ayu Putu Widiati (Warmadewa Press, 2021)
Health is an important aspect and become a measure of the welfare of the people of a country. The development of national development, one of them is in the health sector, must be in accordance with and based on Pancasila and the 1945 Constitution of the Republic of Indonesia. The purpose of this research is to reveal the government's responsibility for handling Covid-19 patients and legal protection for Covid-19 patients medical services in the hospital. The research method used is normative. The assessment is carried out by means of a literature study which is specifically related to law in the health sector. The data sources used were prmiary, secondary and tertiary sources and were analyzed systematically. The result of this research indicates that the responsibility of the government for Covid-19 patients provides rights to patients regulated in related regulations. If the government and parties who violate the rights that should be received by Covid-19 patients, they can be subject to sanctions in accordance with applicable regulations. Legal protection or the issuance of legal rules regarding the rights of Covid-19 patients aims to protect the community itself.